GLOBAL FINANCIAL INSTITUTIONS AND THE HISTORY OF THEIR FORMATION - Abdulhamidov , Abdulajan (Scientific practical conference, 2026)
This text describes the activities of international financial institutions and multilateral development banks, the reasons for their establishment and their role in global economic development. International financial institutions are established by several countries and operate under international law. Meanwhile, multilateral development banks provide loans, grants and technical assistance to support development. They play an important role in financing infrastructure projects, attracting investment, and stimulating economic growth. The text also provides information on the process of reforming these banks in the 2020s, initiatives aimed at increasing their financial stability and functioning as a more efficient system in development projects.